2019
DOI: 10.1002/dc.24351
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymph node metastasis of ovarian dysgerminoma: A case report with fine needle aspiration cytology

Abstract: Dysgerminoma is a rare germ cell tumor, accounting for 1% to 2% of all malignant ovarian tumors. Here, we report a case of dysgerminoma diagnosed by aspiration cytology of a cervical lymph node. A 20‐year‐old woman presented with an abdominal mass and left cervical swelling. CT revealed a large pelvic tumor, along with a nodular lesion on the left side of neck. Fine needle aspiration (FNA) cytology of a cervical lymph node showed large atypical cells and small lymphocytes. Immunocytochemical staining on cell b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…7 , 11 In addition, extra-abdominal lymph nodes such as supraclavicular, cervical lymph nodes, and as well as other nodes, may be involved. 11 - 13 In this case, retroperitoneal solid lesions likely of lymph node origin were seen in USG of the whole abdomen which is suggestive of pre-aortic lymph node metastasis. The patient was asked to be on regular follow-up but she visited to us only 11 months after her surgery which made it difficult to plan for further treatment.…”
Section: Discussionmentioning
confidence: 65%
“…7 , 11 In addition, extra-abdominal lymph nodes such as supraclavicular, cervical lymph nodes, and as well as other nodes, may be involved. 11 - 13 In this case, retroperitoneal solid lesions likely of lymph node origin were seen in USG of the whole abdomen which is suggestive of pre-aortic lymph node metastasis. The patient was asked to be on regular follow-up but she visited to us only 11 months after her surgery which made it difficult to plan for further treatment.…”
Section: Discussionmentioning
confidence: 65%
“…The incidence of brain metastasis in gonadal GCTs varies between 2% to 16%, as shown by diverse studies. The predominant metastatic subtypes are choriocarcinoma, yolk sac tumor, and embryonal carcinoma ( 14 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common metastases of dysgerminoma are the peritoneal cavity, omentum (86%), pelvis and abdomen [11,23], and retroperitoneal lymph node [11,23,24]. Furthermore, extra-abdominal lymph nodes such as para-aortic, [23,25,26], supraclavicular [11] and cervical lymph nodes [26][27][28] may be involved. Distant hematogenous metastases develop in the bones [29][30][31], lungs (15%) [24], liver [29,31], kidneys [29], adrenal glands [31], mammary glands [32], cranium, brain, dura mater and intra-axial [24,33,34], pancreas [29], heart and skin [32].…”
Section: Discussionmentioning
confidence: 99%
“…A study performed in 2020 by Maekawa et al revealed a cervical lymph node metastasis from OD on fine needle aspiration cytology [28]. Kumar et al reported that the prevalence of lymph node metastasis predicts recurrences and metastasis in patients with OD [42] Epidemiological data showed that OD can be associated with some factors, such as (i) dysontogenic gonads; (ii) paraneoplastic hypercalcemia or (iii) endocrine disorders.…”
Section: Discussionmentioning
confidence: 99%